2010
DOI: 10.1007/s10439-009-9884-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Airway Gas Exchange on the Multiple Inert Gas Elimination Technique: Theory

Abstract: The multiple inert gas elimination technique (MIGET) provides a method for estimating alveolar gas exchange efficiency. Six soluble inert gases are infused into a peripheral vein. Measurements of these gases in breath, arterial blood, and venous blood are interpreted using a mathematical model of alveolar gas exchange (MIGET model) that neglects airway gas exchange. A mathematical model describing airway and alveolar gas exchange predicts that two of these gases, ether and acetone, exchange primarily within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
(81 reference statements)
0
8
0
Order By: Relevance
“…However, in contrast to pCO 2 , there was a small (~4.5%) but significant (P < 0.001) increase in alveolar acetone concentrations at forced expiration. A possible explanation could be, that under the special conditions of forced expiration exchange phenomena from bronchial epithelium contributed to the exhaled concentrations of acetone3536. Recent studies have also suggested partial exchange of VOCs with good water solubility and relatively higher blood:air partition coefficient within the bronchial tree in certain conditions such as increased bronchial perfusion or elevated exhalation flow363738.…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to pCO 2 , there was a small (~4.5%) but significant (P < 0.001) increase in alveolar acetone concentrations at forced expiration. A possible explanation could be, that under the special conditions of forced expiration exchange phenomena from bronchial epithelium contributed to the exhaled concentrations of acetone3536. Recent studies have also suggested partial exchange of VOCs with good water solubility and relatively higher blood:air partition coefficient within the bronchial tree in certain conditions such as increased bronchial perfusion or elevated exhalation flow363738.…”
Section: Discussionmentioning
confidence: 99%
“…This "common knowledge" has first been put into question in the field of breath alcohol testing, revealing observable blood-breath concentration ratios of ethanol during tidal breathing that are unexpectedly high compared to the partition coefficient derived in vitro [13]. Similarly, excretion data (i.e., the ratios between steady state partial pressures in expired air and mixed venous blood) of highly water soluble compounds (including the MIGET test gas acetone) have been shown to underestimate the values anticipated by treating the airways as an inert tube [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Conservation of mass in this reduced coordinate system becomes ∂ A ρ̅ / ∂ t = −∂ J / ∂ x − α, where α represents the mass loss rate; it is typically taken to be negligible in the conducting airways for O 2 and CO 2 transport. For other gases, this may not be valid; airway gas exchange has recently been investigated with respect to gas exchange measurements probed with MIGET (Anderson and Hlastala, 2010; see also Hlastala 2003). They found significant effects of airway exchange (especially ether and acetone) on estimated ventilatory distributions, while perfusion distributions were relatively unaffected.…”
Section: Ii2 the Convection-diffusion Equationmentioning
confidence: 99%